Virtual “Walk with Mary”: a popular part y in dialogue with digital (Revista Internacional de Folkcomunicação, 2020)
The Catholic Church has always sought to be connected with the media and the COVID-19 pandemic has further strengthened the religious institution's ties to social media. In this scenario, popular festivals also needed to reconfigure their practices to meet the need for isolation, which included the even stronger presence of these celebrations in the digital environment. In this context, the object of this research is the “Walk with Mary”, a traditional Catholic procession held in Fortaleza, which took place in virtual format in 2020. The methodology used is netnography, through the analysis of the comments of the faithful during the live broadcast of the religious festival. It was possible to observe how the participants appropriated these spaces to manifest devotional and voting practices, which demonstrates the communication opportunities that religiosity has experienced in the digital age. Social networks; Popular festival; Internet; Religiosity; Folkcommunication.